Children of parents with depression or anxiety: Long‐term follow‐up, causality and resilience - Henrik Larsson (Wiley, 2023)
Abstract Three papers in the December issue (2023) of JCPP Advances focus on children of parents with depression or anxiety. They highlight the value of using prospective longitudinal data to improve the understanding about the development of children of parents with depression or anxiety from early childhood to young adulthood. They contribute to an advanced understanding of long‐term outcomes, causality and resilience for children of parents with depression or anxiety.